The advertised diet: an examination of the extent and nature of food advertising on Australian television - Roberts, M.; Pettigrew, Simone; Chapman, K.; Quester, P.; Miller, C. (Australian Health Promotion Association, 2013)
Issues addressed: The aim of the present study was to describe food advertising and expenditure on Australian television, and to conduct an audit to assess what proportion of food and beverage television advertisements was consistent with dietaryrecommendations.Methods: Data were acquired from a national media monitoring company for advertisements broadcast in five major Australian cities from 1 September 2010 to 31 October 2010. Content analysis was undertaken on these advertisements and the advertised foods were assessed against the Australian Guide to Healthy Eating. The data also included advertising expenditures.Results: Most advertised foods were non-core foods (63%), with few advertisements for fruits and vegetables (6%). Advertisements for non-core foods were significantly more frequent during prime time viewing periods (71% vs 60%; P < 0.01). High levels of advertising for fast food (28%) and non-core beverages (24%) were recorded.Conclusions: The present study found that the foods advertised during the data-collection period were inconsistent with the recommended diet. There are clear areas for policy concern given that the majority of recorded advertisements were for foods classified as ‘occasional foods’, there were low levels of advertising for fruit and vegetables, and there were no social marketing messages to support healthy eating.